Zu viel, zu wenig oder genau richtig? Die Reform der Bankenregulierung nach der Finanzkrise - Andreas Dombret (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– Scholars, politicians and regulators have been racking their brains over this problem since 2007, the year the financial crisis broke out. The question of whether a fi-nancial system can even be stable in the first place has also emerged. And yet if there is one thing all know, it is that there will never be a completely stable, completely crisis-proof financial system in the real world. However, many share the conviction that, if nothing else, a finan-cial system can be made a little less vulnerable, thereby containing the fallout from crises - provided the right solutions are found. The G20 countries have travelled a long and often rocky road in order to make the financial system more stable. Andreas Dombret makes the follow-ing three points: First, he discusses the regulatory princi-ple that was supposed to guide post-crisis reforms: if we assume that the idea of a 100 % stable financial system is utopian, then reforms should be conducted to prevent financial bubbles from being created by misevaluation and excessive leverage while crisis-proofing banks. His second point concerns equilibrium and an assessment of these reforms. As supervisor and regulator, he is naturally partial and convinced that regulation has taken the path of the golden mean: in his assessment, financial stability and risk appetite are being treated equally. And this is why, once Basel III has been finalized, he argues for a regulatory break for now. Yet - and this is his third point - reforms will have the desired effect if, and only if, the rules are also credibly and rigorously implemented and applied.
Keywords: E58; G18; G28; N22; N24; N42; N44; 330